Analysis of Work Accident Prevention during the Loading and Unloading Process on MV. Tanto Nusantara at Tanjung Priok Port: Analisis Pencegahan Kecelakaan Kerja saat Bongkar Muat di KM. Tanto Nusantara pada Pelabuhan Tj. Priok - Nurmala, Eka; Laju, I Kadek; Dahlan, Harris R.; Muda, Indra; Syaputra, M. (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
Occupational safety and health play a crucial role in the workplace, significantly impacting a company's productivity and success. Companies need to implement specific techniques and tools to foster a safe work environment that promote occupational health and safety. Many organizations now adopt the philosophy of "safety first," ensuring workers have access to robust safety measures. Work accidents can occur anywhere—at the workplace, while commuting, or even at home. Preventing these accidents requires adherence to occupational safety instructions provided by the company and the proper use of safety equipment that meets established standards. If safety protocols are not executed effectively or according to well-defined Standard Operating Procedures (SOPs), it can lead to negative consequences for both the company and its employees. Such lapses can result in delayed work and decreased productivity, ultimately causing financial losses for the company and hindering workers' performance. This study employs a qualitative approach, allowing for an in-depth exploration and understanding of the subject from the perspectives of the research participants. The findings of this research are as follows: 1) Loading and Unloading Procedures at KM Tanto Nusantara: These procedures include initial preparations, determining the location and position of the containers, the unloading process, the loading process, final inspections and reporting, as well as the completion of administrative tasks and the return of the ship; 2) Obstacles During Loading and Unloading at KM Tanto Nusantara: Challenges faced include extreme weather conditions, limited infrastructure and port facilities, technical issues with equipment, data inaccuracies, constraints related to human resources, heavy traffic at the port, security concerns, and changes in regulations or customs procedures; and 3) Solutions to Address Obstacles and Prevent Work Accidents During Loading and Unloading at KM Tanto Nusantara: Proposed solutions involve utilizing advanced technology and equipment, enhancing workforce training and skills, implementing strict safety standards and procedures, managing weather and external factors, organizing storage areas and supporting equipment, conducting regular compliance monitoring and safety audits, and ensuring adherence to regulations.